Renninger’s Gedankenexperiment, the collapse of the wave function in a rigid quantum metamaterial and the reality of the quantum state vector - Savel’ev, Sergey E. (Sci Rep, 2018)
A popular interpretation of the “collapse” of the wave function is as being the result of a local interaction (“measurement”) of the quantum system with a macroscopic system (“detector”), with the ensuing loss of phase coherence between macroscopically distinct components of its quantum state vector. Nevetheless as early as in 1953 Renninger suggested a Gedankenexperiment, in which the collapse is triggered by non-observation of one of two mutually exclusive outcomes of the measurement, i.e., in the absence of interaction of the quantum system with the detector. This provided a powerful argument in favour of “physical reality” of (nonlocal) quantum state vector. In this paper we consider a possible version of Renninger’s experiment using the light propagation through a birefringent quantum metamaterial. Its realization would provide a clear visualization of a wave function collapse produced by a “non-measurement”, and make the concept of a physically real quantum state vector more acceptable.